2020
DOI: 10.1177/0198742920973213
|View full text |Cite
|
Sign up to set email alerts
|

A Study of One State’s School District Physical Restraint and Seclusion Policies

Abstract: This descriptive analysis of policy content examined local school district policies on physical restraint and seclusion in one Midwestern state that did not have state legislation on these topics to determine whether districts had policies and, if so, whether their content included recommended principles from the U.S. Department of Education. No previous research has addressed district policies. A maximum variation sample of 90 districts was examined to determine whether policies were in place, whether recomme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…In spite of the call in U.S. Department of Education guidelines for states and school districts to enact policies in accord with its 15 principles, a study of local district policies found widely varying degrees to which the principles have been incorporated (Gagnon et al, 2017). Often, the most important components, such as the requirement that these procedures be only used in crisis situations where injury is possible, are missing from these policies (Van Acker, 2020; Van Acker et al, 2020).…”
Section: Lack Of Laws and Policies Relating To Seclusionmentioning
confidence: 99%
“…In spite of the call in U.S. Department of Education guidelines for states and school districts to enact policies in accord with its 15 principles, a study of local district policies found widely varying degrees to which the principles have been incorporated (Gagnon et al, 2017). Often, the most important components, such as the requirement that these procedures be only used in crisis situations where injury is possible, are missing from these policies (Van Acker, 2020; Van Acker et al, 2020).…”
Section: Lack Of Laws and Policies Relating To Seclusionmentioning
confidence: 99%
“…Thus, attention needs to be paid to local policies and procedures, in addition to state and federal. For example, one recent study showed significant variation of local school district policies within one state (Van Acker et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…(National Disability Rights Network, 2009, p. 22) The report's authors recommended banning seclusion and prone restraints in educational settings (i.e., a student being restrained face down on their stomach), in addition to only using restraint in situations where there was immediate harm to the student or staff. These solutions have been suggested by other scholars (Gagnon et al, 2021;Marx & Baker, 2017;Simonsen et al, 2014;Van Acker et al, 2021) but have yet to be included in federal law or are not consistently applied within many state and district policies and regulations.…”
mentioning
confidence: 99%